Priority effects and competition by a native species inhibit an invasive species and may assist restoration. Issue 23 (4th November 2020) - Yu, Hanxia; Yue, Maofeng; Wang, Cui; Le Roux, Johannes J.; Peng, Changlian; Li, Weihua
Abstract: Selecting native species for restoration is often done without proper ecological background, particularly with regard to how native and invasive species interact. Here, we provide insights suggesting that such information may greatly enhance restoration success. The performance of the native vine, Pueraria lobata, and that of the invasive bitter vine, Mikania micrantha, were investigated in South China to test how priority effects (timing and rate of germination and seedling growth) and competition (phytochemical effects and competitive ability) impact invasive plant performance. We found that, in the absence of competition, the germination rate of M. micrantha, but not of P. lobata, was significantly affected by light availability. P. lobata seedlings also performed better than those of M. micrantha during early growth phases. Under competition, negative phytochemical effects of P. lobata on M. micrantha were strong and we found M. micrantha to have lower performance when grown with P. lobata compared to when grown by itself. Relative interaction indexes indicated that, under interspecific competition, P. lobata negatively affected (i.e., inhibited) M. micrantha, whereas M. micrantha positively affected (i.e., facilitated) P. lobata . Higher photosynthetic efficiency and soil nutrient utilization put P. lobata at a further advantage over M. micrantha . Field trails corroborated these experimental findings, showing little recruitment of M. micrantha in previously invaded and cleared field plots that were sown with P. lobata . Thus, P. lobata is a promising candidate for ecological restoration and for reducing impacts of M. micrantha in China. This research illustrates that careful species selection may improve restoration outcomes, a finding that may also apply to other invaded ecosystems and species. Abstract : P. lobata negatively affected M. micrantha, whereas M. micrantha positively affected P. lobata under interspecific competition. P. lobata is a promising candidate for ecological restoration and for reducing impacts of M. micrantha .